2007
DOI: 10.1007/s00542-007-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of heat transfer in a manifold microchannel heat sink with high efficient copper heat spreader

Abstract: A manifold microchannel heat sink integrated with a high efficient copper heat spreader is presented. A series analysis of three-dimensional fluid flow and heat transfer performance in this mirochannel heat sink and conventional structure are performed by CFX commercial software package. The temperature difference along the flow direction in the new microchannel heat sink is less than that of the conventional microchannel heat sink due to effect of the transverse channel arrays. The maximum heat flux input of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Wang and Ding (2008) investigated the microchannel heat exchanger by commercial code and showed 75% higher cooling performance than conventional heat sink by employing traverse microchannel arrays. Colegan et al (2007) developed high performance silicon microchannel heat exchanger by using water and fluorinated fluid as a coolant.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Ding (2008) investigated the microchannel heat exchanger by commercial code and showed 75% higher cooling performance than conventional heat sink by employing traverse microchannel arrays. Colegan et al (2007) developed high performance silicon microchannel heat exchanger by using water and fluorinated fluid as a coolant.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng observed that the stacked microchannels having passive structures perform better than plain microchannels. Wang and Ding did the performance analysis of manifold microchannel heat sink integrated with a high efficient copper heat spreaders. Baghernezhad and Abouali in 2008 presented their investigation done for different types of the grooves fabricated in the microchannel surfaces and concluded that grooves of arc shapes performance better compared with rectangular shape grooves.…”
Section: Introductionmentioning
confidence: 99%
“…) and numerical (e.g., Refs. ) researches have been carried out regarding microchannel cooling, reviewed by Tullius and colleagues …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] and numerical (e.g., Refs. [17][18][19][20] researches have been carried out regarding microchannel cooling, reviewed by Tullius and colleagues. 3 For ventilation and refrigeration systems, flow cavitation is a phenomenon that leads to noise, wear and loss of system efficiency and therefore should be avoided.…”
Section: Introductionmentioning
confidence: 99%